Management of Local Religious and Diniyah Curriculum Implementation in Strengthening Students’ Religious Character - Muhammad Rifan; Nurfadlilah Muhyi; Ahmad Syaifulloh; Gusli Bambang Irawan (Journal of Educational Management Research, 2025)
This study aims to examine the management of local religious and Diniyah curriculum implementation in strengthening students’ religious character, while identifying its impacts, supporting factors, and challenges. Employing a qualitative descriptive approach, data were collected through observations, in-depth interviews, and document analysis in selected primary and secondary schools that implement local religious and Diniyah programs. Informants included school principals, teachers of local religious and Diniyah subjects, and students, selected using purposive and snowball sampling techniques. Data were analyzed interactively through data reduction, data display, and conclusion drawing with verification. The findings indicate that the implementation of local religious and Diniyah curriculum is systematically integrated into intramural, co-curricular, and extracurricular activities, positively influencing students’ religious character, such as increased discipline in worship, honesty, responsibility, and social care. The successful implementation is supported by strong community religiosity, engagement of religious institutions, and educational policy. However, challenges remain, including limited qualified educators, infrastructure constraints, and students’ diverse religious backgrounds. Overall, the study highlights that effective management of local religious and Diniyah curriculum can serve as a model for character education based on Islamic values in broader educational contexts.